Copy Number Variants Are Ovarian Cancer Risk Alleles at Known and Novel Risk Loci. (10th October 2022) - DeVries, Amber A; Dennis, Joe; Tyrer, Jonathan P; Peng, Pei-Chen; Coetzee, Simon G; Reyes, Alberto L; Plummer, Jasmine T; Davis, Brian D; Chen, Stephanie S; Dezem, Felipe Segato; Aben, Katja K H; Anton-Culver, Hoda; et al.
Abstract: Background: Known risk alleles for epithelial ovarian cancer (EOC) account for approximately 40% of the heritability for EOC. Copy number variants (CNVs) have not been investigated as EOC risk alleles in a large population cohort. Methods: Single nucleotide polymorphism array data from 13 071 EOC cases and 17 306 controls of White European ancestry were used to identify CNVs associated with EOC risk using a rare admixture maximum likelihood test for gene burden and a by-probe ratio test. We performed enrichment analysis of CNVs at known EOC risk loci and functional biofeatures in ovarian cancer–related cell types. Results: We identified statistically significant risk associations with CNVs at known EOC risk genes; BRCA1 ( P EOC  = 1.60E-21; OREOC  = 8.24), RAD51C ( P high-grade serous ovarian cancer [HGSOC]  = 5.5E-4; odds ratio [OR]HGSOC  = 5.74 del), and BRCA2 ( P HGSOC  = 7.0E-4; ORHGSOC  = 3.31 deletion). Four suggestive associations ( P  < .001) were identified for rare CNVs. Risk-associated CNVs were enriched ( P  < .05) at known EOC risk loci identified by genome-wide association study. Noncoding CNVs were enriched in active promoters and insulators in EOC-related cell types. Conclusions: CNVs in BRCA1 have been previously reported in smaller studies, but their observed frequency in this large population-based cohort, along with the CNVs observed at BRCA2 and RAD51C gene loci in EOC cases, suggests that these CNVs are potentially pathogenic and may contribute to the spectrum of disease-causing mutations in these genes. CNVs are likely to occur in a wider set of susceptibility regions, with potential implications for clinical genetic testing and disease prevention.